The influence of financial management practices, board effectiveness and accountability towards performance: empirical test of non-profit organizations / NurAfifah Shuib, Jamaliah Said and Ruhaya Atan - Shuib, NurAfifah; Said, Jamaliah; Atan, Ruhaya (Universiti Teknologi MARA Cawangan Selangor, 2013)
Non-profit organizations (NPOs) rely on a variety of activities and resource providers to support their mission-related work. Prior researches on the factors influencing the performance of non-profit organizations were largely based on conceptual argument with no empirical support. The Resource-Dependency Theory (RDT) has suggested that external resources of organizations affect NPOs performance. In the light of RDT, this paper examines how financial management practices, level of accountability and board effectiveness affect the performance of NPOs. Based on the analysis from 107 questionnaires received from top level management of NPOs, the finding revealed that there is significant positive relationship between the financial management practices, board effectiveness and the performance of NPOs. This provides an indication that for NPOs to sustain and remain relevant, they need to adopt adequate level of financial management and appoint only board that are actively involved in NPOs strategic direction. This study is important to provide guidelines to NPOs on the strategies that need to be adopted to enhance their performance.